Managing smallholder teak plantations: field guide for farmers - Pramono, A.A.; Fauzi, M.A.; Widyani, N.; Heriansyah, I.; Roshetko, James M. (Center for International Forestry Research, 2011)
The typical practice by smallholder teak growers of letting trees grow without management input has resulted in poor quality plantations. Various questions arise when farmers start to better manage their teak plantations. This book provides practical guidance in addressing these questions by explaining in detail the techniques of parent tree selection, seed preparation, seedling production, planting, fertilising, thinning, pruning, controlling pest and disease and harvesting. To be more easily understood, the descriptions are complemented by illustrations, photographs or tables. This manual is somewhat different from other teak silvicultural manuals because it is written in simple language, specifically designed for smallholder teak farmers. Specific problems faced in managing teak plantations are often not addressed in existing manuals. How to plant teak on rocky land, how to thin trees in uneven-aged stands, how to maintain coppices from stumps, and how to harvest trees with a need-based cutting system are addressed. Some techniques discussed are adopted from farmers’ traditional knowledge in Gunungkidul.